Production and characterization of polyvinyl alcohol films containing essential oil - Unlu, Nihan; Ozgen, Arzu; Aksu Canbay, Canan (Taylor & Francis Ltd, 2024)
Packaging plays an important role in protecting foodstuffs against physicochemical damage and microbial activity, as well as extending shelf life. In recent years, petrochemical compounds that cause environmental pollution and contamination due to their non-biodegradability have been replaced by biocompatible polymer-based films in the food packaging industry. Due to aromatic essential oils (EO), various biological activities, and their potential to replace chemical preservatives in the field of food preservation, Star Anise essential oil, which has properties, such as free radical scavenger, antibacterial, antifungal and antiviral, was used as an additive in this study. Biodegradable and biocompatible polyvinyl alcohol (PVA) polymer was used as the matrix and polymer-based films were produced in 3 different concentrations. Spectral analysis, structural, chemical, and thermal characterizations, and surface morphologies of the produced films by the direct incorporation method were examined. In addition, the antibacterial activities of the films on Staphylococcus epidermidis ATCC 12228, Escherichia coli ATCC 25922, and Acinetobacter baumannii ATCC BAA 747 bacteria were investigated. As a result of the examinations, it was determined that an interfacial interaction occurred between the matrix and the filler, and the produced films were thermally resistant and showed antibacterial activity against Gram (+)/Gram (-) bacteria. Consequently, it can be concluded that PVA films containing Star Anise essential oil present a prospective substitute in a variety of industrial packaging systems, including those for food, medicine, and cosmetics.
Keywords: Antibacterial polymer films; star anise essential oil (EO); antibacterial activity; production of polymer films; characterization of antibacterial polymer films